2006
DOI: 10.1152/ajpregu.00455.2005
|View full text |Cite
|
Sign up to set email alerts
|

Putative role of the NTS in alterations in neural control of the circulation following exercise training in rats

Abstract: Exercise training (ExTr) has been associated with alterations in neural control of the circulation, including effects on arterial baroreflex function. The nucleus tractus solitarius (NTS) is the primary termination site of cardiovascular afferents and critical in the regulation of baroreflex-mediated changes in heart rate (HR) and sympathetic nervous system outflow. The purpose of the present study was to determine whether ExTr is associated with alterations in neurotransmitter regulation of neurons involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 49 publications
(93 reference statements)
6
54
0
Order By: Relevance
“…Exercise training for 8 wk or more increases the activity of citrate synthase (29,30,32). Indeed, our exercise protocol was not enough to produce the same metabolic muscular changes observed in trained animals.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Exercise training for 8 wk or more increases the activity of citrate synthase (29,30,32). Indeed, our exercise protocol was not enough to produce the same metabolic muscular changes observed in trained animals.…”
Section: Discussionmentioning
confidence: 84%
“…Evidence suggested that the exercise training can reduce tonic GABA-mediated inhibition of intermediate NTS neurons involved in the control of heart rate that could explain the decrease in the resting values (32). Reduction of the resting tail pressure after swimming exercise compared with initial preexercise values could be attributed to blunted baroreflex-mediated sympathoexcitation (12,13,27,28,32).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is unknown whether exercise training could ameliorate the reduction in BRSinc caused by altered central autonomic integration associated with withdrawal of female sex hormones. However, it has been shown that exercise training has potency to modulate intrinsic properties of several autonomic-related nucleus in central nervous system (Jackson et al 2005;Mueller and Hasser 2006). Moreover, it is well known that exercise training increases BRSinc in pathological conditions such as hypertension (Somers et al 1991), myocardial infarction (La Rovere et al 2002), and heart failure (Liu et al 2002).…”
Section: Measurement Of Arterial Pressurementioning
confidence: 99%
“…Preoperation and sham operation groups were used as control. ventrolateral medulla (RCLM) [16][17][18][19][20][21][22][23][24], the nucleus of solitary tract (NTS) [7,25] and paraventricular nucleus (PVN) [26]. The PVN connects these areas in the brain involved in cardiovascular function, forming important neuroendocrine and autonomic modulation, which further modulates the homeostasis of the body through the brain stem, spinal cord, median eminence and posterior pituitary.…”
Section: Discussionmentioning
confidence: 99%